Local Kondo scattering in 4d-electron RuOx nanoclusters on atomically-resolved ultrathin SrRuO3 films. Issue 39 (30th September 2021) - Song, Chuangye; Bo, Tao; Liu, Xin; Guo, Pengjie; Meng, Sheng; Wu, Kehui
Abstract : Emergent Kondo scattering features are observed on RuO x clusters located on the non-reconstructed SrRuO3 ultrathin films with SrO-termination by as revealed by combined STM/STS and DFT calculations. Abstract : Perovskite SrRuO3 is a unique 4d transition metal oxide with coexisting spin–orbit coupling (SOC) and electron–electron correlation. However, the intrinsic, non-reconstructed surface structure of SrRuO3 has not been reported so far. Here we report an atomic imaging of the non-reconstructed, SrO-terminated SrRuO3 surface by scanning tunneling microscopy/spectroscopy. Moreover, a Kondo resonant behavior is revealed in RuO x clusters located on top of the nonmagnetic SrO surface layer. The density functional theory calculations confirm that RuO x clusters possess localized 4d-electron-involved spin moments and hybridize with the conduction electrons in the metal host, resulting in the appearance of the Kondo resonance features around the Fermi level. Our work demonstrates that artificially-engineered transition metal oxides provide new opportunities to explore the Kondo physics in 4d multi-orbital systems.